A reconfigurable multi-terrain adaptive casualty transport aid base on Watt II six-bar linkage for industrial environment - Jiao, Zongqi; Wang, Haibin; Fei, Cuizhi; Wang, Liang; Yuan, Jincan; Meng, Qiaoling; Lu, Xuhua (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: This paper presents the Reconfigurable Multi-Terrain Adaptive Casualty Transport Aid (RMTACTA), an innovative solution addressing the critical need for rapid and safe pre-hospital casualty transport in industrial environments. The RMTACTA, leveraging the Watt II six-bar linkage, offers enhanced adaptability through six modes of motion, overcoming the limitations of traditional stretchers and stretcher vehicles by facilitating navigation across narrow and challenging terrains. Methods: The RMTACTA's design incorporates two branching four-bar mechanisms to form a compact, reconfigurable Watt II six-bar linkage mechanism. This setup is controlled via a single remote rope, allowing for easy transition between its multiple operational modes, including stretcher, stretcher vehicle, folding, gangway-passing, obstacle-crossing, and upright modes. The mechanical design and kinematics of this innovative linkage are detailed, alongside an analysis of the optimal design and mechanical evaluation of rope control. Results: A prototype of the RMTACTA was developed, embodying the proposed mechanical and kinematic solutions. Preliminary tests were conducted to verify the prototype's feasibility and operability across different terrains, demonstrating its capability to safely and efficiently transport casualties. Discussion: The development of the proposed Reconfigurable Multi-Terrain Adaptive Casualty Transport Aid (RMTACTA) introduces a novel perspective on the design of emergency medical transport robots and the enhancement of casualty evacuation strategies. Its innovative application of the Watt II six-bar linkage mechanism not only showcases the RMTACTA's versatility across varied terrains but also illuminates its potential utility in critical scenarios such as earthquake relief, maritime rescue, and battlefield medical support.